2012
DOI: 10.1039/c2cp40931c
|View full text |Cite
|
Sign up to set email alerts
|

Stability and iron coordination in DNA adducts of Anthracycline based anti-cancer drugs

Abstract: There is evidence that the interaction of the α-ketol group of the Doxorubicin and Epirubicin anti-cancer drugs with Fe(III) generates hydroxyl radicals under aerobic conditions, causing cardiotoxicity in patients. Considering that the formation of DNA adducts is one of the main targets of Anthracycline drugs, we have in the present study characterized several [Anthracycline-DNA]Fe(III) complexes with respect to their stability and Fe(III) coordination, by means of MD simulations. Iron is found to coordinate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…At neutral pH, the aglycone part is neutral, whereas the daunosamine moiety is protonated. , Deprotonation of the phenolic OH groups of the aglycone ring B upon pH increase (p K values of 10.16 for C 11 –OH and 13.2 for C 6 –OH) produces spectral modifications quite similar to those of Figure b. , This finding suggests that DOX incorporation into the MOF frame is mediated by deprotonation of hydroxyl groups of the aglycone moiety, most likely involved in coordination to Fe(III) centers. Further support for this conclusion comes from the similarity of the UV–vis absorption spectra of DOX-MOF mixtures to those of DOX solutions with free Fe(III) ions, in which up to three drug molecules are coordinated with release of one proton per bound unit. , Various binding modes of DOX to Fe(III) ions have been suggested: bidentate chelation at the quinone-hydroquinone sites of the C–B rings, ,, coordination to the C14 hydroxyl group of the α-ketol side chain, and formation of a cage-like structure involving the two quinone oxygens, an α-hydroxy terminal group, and the ketone of the C9 side group . Interactions of Fe 3+ with daunosamine moiety and the C4 methoxy group have also been indicated to promote the anthracycline-iron complexation. , Close inspection of the spectra in Figure b reveals the presence of quasi-isosbestic points at 420 and 530–540 nm for MOF content ≤0.1 mg/mL, which are lost at higher MOF contents.…”
Section: Resultsmentioning
confidence: 97%
“…At neutral pH, the aglycone part is neutral, whereas the daunosamine moiety is protonated. , Deprotonation of the phenolic OH groups of the aglycone ring B upon pH increase (p K values of 10.16 for C 11 –OH and 13.2 for C 6 –OH) produces spectral modifications quite similar to those of Figure b. , This finding suggests that DOX incorporation into the MOF frame is mediated by deprotonation of hydroxyl groups of the aglycone moiety, most likely involved in coordination to Fe(III) centers. Further support for this conclusion comes from the similarity of the UV–vis absorption spectra of DOX-MOF mixtures to those of DOX solutions with free Fe(III) ions, in which up to three drug molecules are coordinated with release of one proton per bound unit. , Various binding modes of DOX to Fe(III) ions have been suggested: bidentate chelation at the quinone-hydroquinone sites of the C–B rings, ,, coordination to the C14 hydroxyl group of the α-ketol side chain, and formation of a cage-like structure involving the two quinone oxygens, an α-hydroxy terminal group, and the ketone of the C9 side group . Interactions of Fe 3+ with daunosamine moiety and the C4 methoxy group have also been indicated to promote the anthracycline-iron complexation. , Close inspection of the spectra in Figure b reveals the presence of quasi-isosbestic points at 420 and 530–540 nm for MOF content ≤0.1 mg/mL, which are lost at higher MOF contents.…”
Section: Resultsmentioning
confidence: 97%
“…Another mechanism of AIC consists in the chelation reaction between iron (III) and the α-ketol group of DOX and epirubicin anticancer drugs [ 40 ]. Moreover, the preventive efficacy of DEX, which is an iron chelator, also supports the hypothesis of iron involvement in ANT cardiotoxicity [ 41 ].…”
Section: Mechanism Of Toxicitymentioning
confidence: 99%
“…The latter is a minor species (≤30%) between pH 6.5-9. In their study of the stability and iron coordination in DNA adducts of anthracycline based anticancer drugs, Eriksson and coworkers 70 found that the Fe 3+ in the [dox-DNA]Fe 3+ system was coordinated to four O-atoms belonging to the [dox-DNA] adduct, and was in addition coordinating five water molecules as well. They suggested that the lower number of O-atoms and the higher number of H 2 O molecules bound to the Fe 3+ were related to a lower binding energy of the metal ion possibly resulting in an increased production of hydroxyl radicals in vivo.…”
Section: Stability Constantsmentioning
confidence: 99%